The Effect of Compensation, Leadership Style, Work Environment on Employee Loyalty of Pt Eldora Entertainment - Putri Aulia Mandhasari; Ahmad Cik; Melati; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to analyze the effect of compensation, leadership style, and work environment on employee loyalty at PT Eldora Entertainment. In addition, this study aims to provide information and input to Human Resources Managers to provide additional insight about the importance of good management so that it will improve the performance and loyalty of PT Eldora Entertainment employees. The data analysis technique uses multiple linear regression analysis and uses the SPSS version 25 program. The data in this study used primary data in the form of questionnaires distributed to employees of P.T Eldora Entertainment. The data analysis technique used is a quantitative method where the results are expressed in numbers. The results obtained that compensation can really make employees more enthusiastic to work and also increase their work loyalty. Leadership style has a positive and significant effect on work loyalty because the work environment has a positive and significant effect on employee loyalty because a comfortable workplace will make them feel calm while working.